AMP-Activated Protein Kinase Induces p53 by Phosphorylating MDMX and Inhibiting Its Activity - He, Guifen; Zhang, Yi-Wei; Lee, Jun-Ho; Zeng, Shelya X.; Wang, Yunyuan V.; Luo, Zhijun; Dong, X. Charlie; Viollet, Benoit; Wahl, Geoffrey M.; Lu, Hua (Molecular and Cellular Biology, 2014)
Article Usage Stats Services MCB Citing Articles Google Scholar PubMed Related Content Social Bookmarking CiteULike Delicious Digg Facebook Google+ Mendeley Reddit StumbleUpon Twitter current issue Spotlights in the Current Issue MCB About MCB Subscribers Authors Reviewers Advertisers Inquiries from the Press Permissions & Commercial Reprints ASM Journals Public Access Policy MCB RSS Feeds 1752 N Street N.W. • Washington DC 20036 202.737.3600 • 202.942.9355 fax • journals@asmusa.org Print ISSN: 0270-7306 Online ISSN: 1098-5549 Copyright © 2014 by the American Society for Microbiology. For an alternate route to MCB .asm.org, visit: MCB